A study of the experiences of international migrants in the UK: a life history approach. - Toalster, Richard. (2012)
Globalisation can no longer be thought of as a term that merely describes the practical, political and procedural networking of capital, commodities and consumers. Working reflexively it networks people, who use the physical, electronic and psychological networks set up to serve the interests of global commerce to travel from one locale to another. Like the cheap frocks, fridges or foodstuffs globalisation has weaned society to expect, these people are a ubiquitous source of labour, prepared to work in our factories and in our fields, servicing our hotel rooms, cleaning our homes and teaching our children. Yet despite this little is known about the lives of international migrants in the UK from their own perspectives, and there is relatively little social research (educational) with which to contextualise the migration statistics or evaluate the claims of the British press.